2020
DOI: 10.1002/ejp.1600
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between body schema, visuospatial perception and pain in patients with spinal cord injury

Abstract: More than half of the patients with spinal cord injury (SCI) suffer chronic neuropathic pain syndromes (Burke, Fullen, Stokes, & Lennon, 2017; Siddall & Middleton, 2015). The mechanisms of neuropathic pain, particularly for below-level pain, remain poorly understood, but may involve the reorganization of the somatosensory systems and changes in body representations related to the massive deafferentation associated with SCI (Jutzeler, Curt, & Kramer, 2015; Osinski, Acapo, Bensmail, Bouhassira, & Martinez, 2019)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…NP is not only associated with higher levels of pain but also brain related sensorimotor dysfunction [ 11 ]. Previous research has shown that body schema alterations are present in a large proportion of people with symptomatic hand OA [ 12 ] with 50% of participants presenting with neglect-like symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…NP is not only associated with higher levels of pain but also brain related sensorimotor dysfunction [ 11 ]. Previous research has shown that body schema alterations are present in a large proportion of people with symptomatic hand OA [ 12 ] with 50% of participants presenting with neglect-like symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Increasing evidence shows that adults with SCI with motor and sensory impairments also experience body awareness deficits. [4][5][6][7][8][9][10][11][12][13][14][15] Body awareness refers to an attentional focus on and awareness of internal body sensations, including whole-body awareness as well as awareness of body parts in relation to each other, and how they are positioned and move in space. 16,17 These motor and sensory impairments, and particularly the loss of awareness of where the limbs are in space, 18 greatly compromise function and mobility.…”
Section: Introductionmentioning
confidence: 99%
“…In sum, these mental body representation deficits hinder functional recovery because the brain does not recognize the body's spatial location to guide movements. [4][5][6][12][13][14]18 Adults who have SCI-related neuropathic pain often have an altered perception related to the size and dimension of the painful and/or sensorimotor-impaired body parts, which justifies the use of CMR to treat neuropathic pain. They also have an altered perception of body weight, pressure, or touch in those body regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15][16][17] Concurrently with reduced or absent sensation, recently, increasing evidence shows that adults with SCI experience deficits in body awareness. [18][19][20][21][22][23][24][25][26][27][28][29][30][31] Body awareness deficits are thought to contribute to the production or maintenance of chronic neuropathic pain. [18][19][20]22,24,25 Body awareness refers to an attentional focus on and awareness of internal body sensations, which includes an awareness of how the body and body parts are positioned and move in space.…”
Section: Introductionmentioning
confidence: 99%